2012
DOI: 10.5402/2012/620951
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Removal of Smear Layer by Two Endodontic Irrigants and Nd:YAG Laser: A Scanning Electron Microscopic Study

Abstract: The aim of this study was to compare the effect of 17% EDTA, 5% maleic acid, and Nd:YAG laser on smear layer removal by SEM. Eighty single-rooted teeth were divided into three groups of 25 according to the final procedure for smear layer removal: irrigation by 17% EDTA or 5% maleic acid or Nd:YAG laser irradiation. The other five teeth was used as control. Roots were sectioned into buccal and lingual parts, and smear layer presence was recorded in the coronal, middle, and apical thirds under SEM. Data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
18
0
2
Order By: Relevance
“…Of these, the use of Nd:YAG (neodymium-doped: yttrium aluminium garnet) laser is gaining popularity. 12,13 This type of laser has been shown to be effective on several applications as preventing erosion, 14 hypersensitivity treatment, 15 cleaning organic debris, 16 and soft tissue surgery. 17 According to literature, the Nd:YAG laser irradiation on dentin promotes its melting thereafter the sealing of the dentin tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the use of Nd:YAG (neodymium-doped: yttrium aluminium garnet) laser is gaining popularity. 12,13 This type of laser has been shown to be effective on several applications as preventing erosion, 14 hypersensitivity treatment, 15 cleaning organic debris, 16 and soft tissue surgery. 17 According to literature, the Nd:YAG laser irradiation on dentin promotes its melting thereafter the sealing of the dentin tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that Nd:YAG laser was less effective in smear layer removal compared to 17% EDTA and 5% maleic acid. 39 Sodium hypochlorite can remove the organic material of the smear layer, but Garberglio et al reported that sodium hypochlorite 1% and 5% were not able to remove the smear layer. 40 In addition, in the present study, the efficiency of laser-activated hypochlorite at a concentration of 5% compared to lower concentrations (2.5, and 1%) was more successful in removing the smear layer (P ≤ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Całko-wicie nieskuteczne okazały się fizjologiczny roztwór soli [28] i woda utleniona [29]. W celu usunięcia warstwy mazistej niezbędne jest stosowanie sekwencji płukania składającej się z podchlorynu sodu, EDTA lub kwasu cytrynowego [30][31][32][33][34]. Carvalho et al [30] oceniali skuteczność podchlorynu sodu, EDTA, soli fizjologicznej i chlorheksydyny w usuwaniu warstwy mazistej.…”
Section: Omówienieunclassified
“…Nie stwierdzili jednak istotnych różnic w części koronowej i środkowej kanału zarówno po użyciu 7% kwasu maleinowego, jak i 17% EDTA. Badania przeprowadzone przez Hasheminia et al [34] wykazały, iż płukanie kanału korzeniowego przez 1 minutę 17% EDTA oraz 5% kwasem maleinowym było bardziej skuteczne w oczyszczaniu zębi-ny kanałowej niż po zastosowaniu lasera Nd:YAG. Podobne wyniki uzyskali inni autorzy [35], stosując laser diodowy w celu usunięcia warstwy mazistej.…”
Section: Omówienieunclassified